Arms and armor collecting in America: history, community and cultural meaning. (21st August 2020) - Witkowski, Terrence H.
Abstract : Purpose: This study aims to present a history and critical analysis of arms and armor collecting in America from the late 19th century until the present day. Design/methodology/approach: The research draws from the literature on arms and armor, from primary written, visual and material evidence, and from the author's long experience as an antique gun and sword collector. Findings: American arms and armor collectors have included men of great wealth, museums and their curators and many enthusiasts of more modest means. Collectors, dealers and curators have created a substantial arms literature. Collectors have organized around various types of artifacts, historical periods and company brands. Dealers, auction houses and manufacturers have provisioned the market with period pieces and reproductions. Originality/value: The history of antique arms and armor collecting is regarded as a social activity where enthusiasts have pursued "serious leisure" through consumption and brand communities. This history is further analyzed as a cultural practice wherein generations of collectors have interpreted the meaning of antique arms and armor.